Knowledges From the South: Reflections on Writing Academically - Munoz-Garcia, Ana Luisa; Lira Muñoz, Andrea Cecilia; Loncon, Elisa (My University, 2022)
In this paper we dialogue on the process of knowledge construction working through and disrupting academic regulations. We build on the reflections born of our own research doing indigenous research of biographies of schooling of Mapuche women, as feminist, indigenous and non-indigenous scholars latinx scholars. We focus on three tensions working on knowledge in and beyond academic spaces. First, the ways in which the knowledges (in plural) that comes from our own biographies usually is left out of academic conversations and moved into what we call invisible zones. Second, the work of translation and translanguaging as we move across language barriers and geographic places in our work, and what these processes afford across geographic and conceptual zones of "north" and "south." Thirdly, the naturalized understanding of knowledge as a product in academic spaces and the ways in which we can reimagine and display complex and complicated ways of doing the research work otherwise.
Keywords: Plural; Translanguaging; Knowledge Production